(untitled) (International Journal of Environmental Sciences, 2025)
Xanthium orientale is widely recognized in traditional medicine for its therapeutic applications; however, the lack of standardized quality control measures poses a risk to its safety, efficacy, and global acceptability. The present study was undertaken to establish comprehensive pharmacognostic and phytochemical standards for the quality assessment and authentication of this medicinal plant. Detailed macroscopic and microscopic evaluations were conducted on the leaves and stem, including powder microscopy to document diagnostic anatomical features. Physicochemical parameters such as total ash, acid-insoluble ash, water and alcohol-soluble extractive values, and loss on drying were determined according to standard procedures. Furthermore, preliminary phytochemical screening of the aqueous and ethanolic extracts of leaves and stems revealed the presence of key secondary metabolites such as alkaloids, flavonoids, tannins, saponins, and glycosides. The data generated from this study provide vital diagnostic and quality control parameters that can serve as a foundation for the development of a pharmacopoeial monograph for Xanthium orientale. This will ensure its safe, effective, and standardized use in herbal formulations and ethnomedicinal practices.